Bovine jugular vein valved xenograft for extracardiac total cavo‐pulmonary connection: The risk of thrombosis and the potential liver protection effect. Issue 4 (29th February 2020) - Ismail, Mohamed F.; Elmahrouk, Ahmed F.; Arafat, Amr A.; Hamouda, Tamer E.; Edrees, Azzahra; Bogis, Abdulbadee; Arfi, Amin M.; Dohain, Ahmed M.; Alkhattabi, Abdullah; Alharbi, Ahmed W.; Shihata, Mohammad S.; Al‐Radi, Osman O.; et al.
Abstract: Background: Currently, non‐valved conduits are preferred for extracardiac total cavo‐pulmonary connection (TCPC). However, previous work has failed to provide objective data comparing the postoperative outcome between non‐valved TCPCs and bovine jugular vein valved xenograft (BJV) TCPCs. Hence, the objective of this study is to compare the postoperative outcomes in extracardiac TCPC patients who received BJV vs synthetic non‐valved conduits and evaluate the effect of BJV on liver fibrosis. Methods: Of 206 patients who had extracardiac TCPC from 2002 to 2017 were divided into three groups. Group A (n = 66) received BJV, group B (n = 37) received PET conduits and group C (n = 103) received polytetrafluoroethylene (PTFE) tube. Study endpoints were hospital outcomes, conduits thrombosis, reinterventions, and survival. Liver stiffness and fibrosis were assessed in eight patients with BJV. Results: Preoperative parameters were comparable among groups. Thrombosis was significantly lower in group C ( P < .0003) but no difference between groups A and B ( P = .951). Reinterventions did not differ significantly among groups (Log‐rank P = .598). Hospital deaths occurred in seven patients (3.4%). There was no difference in survival between groups (Log‐rank P = .221). The median liver stiffness score was 18.65 kPa and the eight patients had advanced liver fibrosis (grade F3‐4) in group A. Conclusion: PTFE is the recommended conduit for TCPC with a lower risk of thrombosis compared to BJV and PET. BJV conduits in TCPC circuits may not protect against liver fibrosis. BJV should not be considered as an option for TCPC.